Assessment of de novo copy-number variations in Italian patients with schizophrenia: Detection of putative mutations involving regulatory enhancer elements. (7th February 2019) - Piluso, Giulio; Monteleone, Palmiero; Galderisi, Silvana; Giugliano, Teresa; Bertolino, Alessandro; Rocca, Paola; Rossi, Alessandro; Mucci, Armida; Aguglia, Eugenio; Andriola, Ileana; Bellomo, Antonello; Comparelli, Anna; et al.
Abstract: Objectives: Variants appearing de novo in genes regulating key neurodevelopmental processes and/or in non-coding cis -regulatory elements (CREs), as enhancers, may increase the risk for schizophrenia. However, CREs involvement in schizophrenia needs to be explored more deeply. Methods: We investigated de novo copy-number variations (CNVs) in the whole-genomic DNA obtained from 46 family trios of schizophrenia probands by using the Enhancer Chip, a customised array CGH able to investigate the whole genome with a 300-kb resolution, specific disease loci at a ten-fold higher resolution, and which was highly enriched in probes in more than 1, 250 enhancer elements selected from Vista Enhancer Browser. Results: In seven patients, we found de novo CNVs, two of which overlapped VISTA enhancer elements. De novo CNVs encompass genes ( CNTNAP2, MAGI1, TSPAN7 and MET ) involved in brain development, while that involving the enhancer element hs1043, also includes ZIC1, which plays a role in neural development and is responsible of behavioural abnormalities in Zic mutant mice. Conclusions: These findings provide further evidence for the involvement of de novo CNVs in the pathogenesis of schizophrenia and suggest that CNVs affecting regulatory enhancer elements could contribute to the genetic vulnerability to the disorder.